2012
DOI: 10.1007/s11802-012-1820-2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and diversity of marine yeasts in Antarctica environments

Abstract: A total of 28 yeast strains were obtained from the sea sediment of Antarctica. According to the results of routine identification and molecular characterization, the strains belonged to species of Yarrowia lipolytica, Debaryomyces hansenii, Rhodotorula slooffiae, Rhodotorula mucilaginosa, Sporidiobolus salmonicolor, Aureobasidium pullulans, Mrakia frigida and Guehomyces pullulans, respectively. The Antarctica yeasts have wide potential applications in biotechnology, for some of them can produce β-galactosidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…b-galactosidases can be applied in the food and pharmaceutical industries, including for sugar reduction in different foods, development of additives for animal and human diets, and bioconversion of milk whey to reduce industrial effluents [69]. Zhang et al [120], reported that the marine Antarctic yeast Tausonia pullulans 17-1 (formerly Guehomyces pullulans) showed highest extracellular b-galactosidase activity in a medium containing only lactose as the carbon source.…”
Section: Other Hydrolytic Enzymesmentioning
confidence: 99%
“…b-galactosidases can be applied in the food and pharmaceutical industries, including for sugar reduction in different foods, development of additives for animal and human diets, and bioconversion of milk whey to reduce industrial effluents [69]. Zhang et al [120], reported that the marine Antarctic yeast Tausonia pullulans 17-1 (formerly Guehomyces pullulans) showed highest extracellular b-galactosidase activity in a medium containing only lactose as the carbon source.…”
Section: Other Hydrolytic Enzymesmentioning
confidence: 99%
“…isolated from diseased marine animals (Wang et al, 2009a, b). In our previous study (Chi et al, 2012b;Liu et al, 2009;Zhang et al, 2012), it was found that some strains of A. pullulans did not produce any melanin during their cell growth. They may be identified to be different new varieties of A. pullulans.…”
Section: #2mentioning
confidence: 96%
“…are ubiquitous species found mainly in soil, including Antarctic soils, water, the phylloplane, wood, and many other plant materials, rocks, monuments and limestone (Urz'| et al, 1999). In recent years, they also have been found to be widely distributed in hypersaline habitats, coastal water, deep sea, marine sediments of Antarctica and mangrove systems (Chi et al, 2012b;Gunde-Cimerman et al, 2000;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the suggestion that yeasts may be better adapted to low temperatures than bacteria (Shivaji and Prasad 2009), many studies have focused on bacteria; however, the number of reports describing the isolation of yeasts from cold environments is increasing (Guffogg et al 2004;Gilichinsky et al 2005;Russell 2006;de Garcia et al 2007;Turchetti et al 2008;Branda et al 2010;Pathan et al 2010;Thomas-Hall et al 2010;Turchetti et al 2011;Carrasco et al 2012;de Garcia et al 2012;Zhang et al 2012;Singh et al 2013). Considering that yeasts provide the benefits of single-cell fermentations and there are a large number of genetic tools to study and manipulate them, psychrophilic and psychrotolerant yeasts have attracted the attention of scientists for their potential application in various industries.…”
Section: Introductionmentioning
confidence: 99%